Impact of wave energy and sediment transport on shoreline changes: A multi-temporal satellite image analysis in Galesong, Takalar Regency, Indonesia - Sakka Sakka; Alimuddin Hamzah Assegaf; Amiruddin Amiruddin; Saaduddin Saaduddin; Siti Nur Azisah Aprianti Azis; Andi Muhammad Imran Ismail (Journal of Degraded and Mining Lands Management, 2025)
Galesong Beach, located in Takalar Regency, South Sulawesi, is a coastal area that has experienced significant shoreline changes due to anthropogenic activities, such as coastal development and land use, and oceanographic factors, particularly wave activity. This study aimed to analyze the magnitude and direction of wave-induced sediment transport and its influence on erosion and accretion rates along Galesong Beach. Wave height was calculated using the Coastal Engineering Manual (CEM) method based on wind data, while sediment transport volume was estimated using the Van Rijn method. Shoreline change rates were identified using Landsat 7 ETM+ and Landsat 8 OLI imagery from 2010 to 2023, analyzed with the Digital Shoreline Analysis System (DSAS) to determine annual erosion and accretion distances and rates. The study area was divided into seven zones, each with varying coastal dynamics. Results showed that monthly wave heights peaked in December, January, and February, ranging from 1.54 to 2.21 m. Sediment transport was estimated at 2,894.9 to 13,703.42 m³/year northward and 5,405.77 to 13,956.26 m³/year southward, resulting in both erosion and accretion. The maximum annual accretion rate reached 10.77 m/year, while the maximum erosion rate was 3.28 m/year. The furthest accretion reached 141.27 m, and the greatest erosion extended to -43.05 m. The highest accretion occurred in North Boddia, while the most severe erosion was found in Bontoloe. This study offers insights into local coastal dynamics and serves as a foundation for effective and sustainable coastal management strategies.